2009
DOI: 10.1101/gad.1761609
|View full text |Cite
|
Sign up to set email alerts
|

p53 isoform Δ113p53 is a p53 target gene that antagonizes p53 apoptotic activity via BclxL activation in zebrafish

Abstract: p53 is a well-known tumor suppressor and is also involved in processes of organismal aging and developmental control. A recent exciting development in the p53 field is the discovery of various p53 isoforms. One p53 isoform is human D133p53 and its zebrafish counterpart D113p53. These N-terminal-truncated p53 isoforms are initiated from an alternative p53 promoter, but their expression regulation and physiological significance at the organismal level are not well understood. We show here that zebrafish D113p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
197
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(226 citation statements)
references
References 27 publications
(62 reference statements)
18
197
3
1
Order By: Relevance
“…We and others have shown that p53 transactivates, in response to stress, the internal p53 promoter giving rise to D133p53 isoforms, thus providing a negative feedback regulation of the p53 response. 3,4,18,23 Altogether, it suggests that p53 and D133p53 isoforms regulate each other's expression in U87 cells. Further experiments will be required to decipher the D133p53-mediated repression of p53 in U87 cells.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We and others have shown that p53 transactivates, in response to stress, the internal p53 promoter giving rise to D133p53 isoforms, thus providing a negative feedback regulation of the p53 response. 3,4,18,23 Altogether, it suggests that p53 and D133p53 isoforms regulate each other's expression in U87 cells. Further experiments will be required to decipher the D133p53-mediated repression of p53 in U87 cells.…”
Section: Discussionmentioning
confidence: 90%
“…21 Moreover, D133p53a inhibits replicative senescence, p53-mediated apoptosis and G1 cell cycle arrest, without preventing p53-promoted G2 cell cycle arrest by regulating gene expression. [2][3][4][5] Altogether, it suggests that p53 isoforms have a key role in carcinogenesis. However, the role of p53 isoforms in angiogenesis was unknown.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations